2021
DOI: 10.3390/nu13051388
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Carbohydrate Ketogenic Diet as an Adjuvant Cancer Therapy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: The role of low-carbohydrate ketogenic diet (LCKD) as an adjuvant therapy in antitumor treatment is not well established. This systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to investigate the efficacy of LCKD as an adjuvant therapy in antitumor treatment compared to non-ketogenic diet in terms of lipid profile, body weight, fasting glucose level, insulin, and adverse effects; Methods: In this study, databases such as PubMed, Web of Science, Scopus, CINAHL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 33 publications
0
35
0
2
Order By: Relevance
“…It might be argued that the ketogenic diet, in combination with standard therapies, has the potential to enhance the antitumor effects of classic chemo- and radiotherapy, with an overall good safety and tolerability, as well as an increase in quality of life [ 22 ]. However, a recent systematic review and meta-analysis of randomized controlled trials revealed inadequate evidence to support the beneficial effects of a ketogenic diet in antitumor therapy [ 23 ]. Moreover, hyperuricemia, hyperlipidemia, and upper abdominal pain have been observed in previous studies with cancer patients [ 11 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It might be argued that the ketogenic diet, in combination with standard therapies, has the potential to enhance the antitumor effects of classic chemo- and radiotherapy, with an overall good safety and tolerability, as well as an increase in quality of life [ 22 ]. However, a recent systematic review and meta-analysis of randomized controlled trials revealed inadequate evidence to support the beneficial effects of a ketogenic diet in antitumor therapy [ 23 ]. Moreover, hyperuricemia, hyperlipidemia, and upper abdominal pain have been observed in previous studies with cancer patients [ 11 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, most applications of KD in human cancers has been as an adjunctive therapy in conjunction with standard of care (i.e., chemotherapy, radiotherapy, and/or surgery). Recent evaluations of the literature conducted by Weber and associates (29 trials) [14], Talib et al (14 trials) [48] and Yang and colleagues (6 trials) [15] Sremanakova and associates [18] (11 trials), Plotti et al [49] (4 trials), and Romer and associates [16] (45 trials) among patients, virtually all being adults (i.e., 18 years of age and older), with a variety of cancers (e.g., glioblastoma, glioblastoma and gliomatosis cerebri, breast cancer, liver, pancreato-biliary cancer, lung and pancreatic, head and neck, colorectal cancer, and mixed cancer sites reported a wide range of favorable outcomes including progression-free survival, increased survival rate, increased rates of response to conventional treatment (i.e., stable disease after 6-week diet) [49], and enhanced quality of life (please see Table 1 for summary of clinical trials). While safe and well-tolerated by the majority of patients, some report side effects, including nausea, constipation, vomiting, hypoglycemia, and fatigue that may compromise adherence to KD [13,20].…”
Section: Clinical Studies Of Kd and Cancermentioning
confidence: 99%
“…While several diets (e.g., vegan, Mediterranean) and dietary regimens (e.g., caloric restriction, intermittent fasting [13]) have been proposed as strategies for cancer prevention and as adjuvant therapies to standard-of-care cancer treatments, we provide a theoretical framework and preliminary evidence from preclinical and clinical studies on how the ketogenic diet (KD) may provide benefits in the prevention and treatment of cancer. Because there are several recent narrative, systematic, and meta-analytic reviews of KD for cancer [14][15][16][17][18], we focus on critically evaluating the state of the knowledge and provide a set of research recommendations to enhance the rigor and replicability of KD-cancer clinical applications and randomized clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…The included studies varied significantly in design and reporting, with a very heterogeneous group of cancer patients that make any results unreliable. Overall, there was no evidence to support the beneficial effects of a low-carbohydrate diet in anti-tumor therapy ( 29 ).…”
Section: Carbohydrate Restriction and Cancer Carementioning
confidence: 99%